Chương II : Số nguyên

LL

Tìm x

(x – 2) . (y + 1) = 23

( – 9) . ( – 36) = 0

– 15x – 18x + 13x = – 4600

NT
2 tháng 5 2020 lúc 13:02

a) Ta có: (x-2)(y+1)=23

⇔x-2;y+1∈Ư(23)

\(\Leftrightarrow\left[{}\begin{matrix}\left\{{}\begin{matrix}x-2=1\\y+1=23\end{matrix}\right.\\\left\{{}\begin{matrix}x-2=-1\\y+1=-23\end{matrix}\right.\\\left\{{}\begin{matrix}x-2=23\\y+1=1\end{matrix}\right.\\\left\{{}\begin{matrix}x-2=-23\\y+1=-1\end{matrix}\right.\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}\left\{{}\begin{matrix}x=3\\y=22\end{matrix}\right.\\\left\{{}\begin{matrix}x=1\\y=-24\end{matrix}\right.\\\left\{{}\begin{matrix}x=25\\y=0\end{matrix}\right.\\\left\{{}\begin{matrix}x=-21\\y=-2\end{matrix}\right.\end{matrix}\right.\)

Vậy: (x,y)∈{(3;22);(1;-24);(25;0);(-21;-2)}

c) Ta có: \(-15x-18x+13x=-4600\)

\(\Leftrightarrow-20x=-4600\)

hay x=230

Vậy: x=230

Bình luận (0)

Các câu hỏi tương tự
LL
Xem chi tiết
DA
Xem chi tiết
H24
Xem chi tiết
PC
Xem chi tiết
H24
Xem chi tiết
NA
Xem chi tiết
TT
Xem chi tiết
NQ
Xem chi tiết
NT
Xem chi tiết